Exploration of Ellsworth Subglacial Lake: A concept paper on the development, organisation and execution of an experiment to explore, measure and sample the environment of a West Antarctic subglacial lake - The Lake Ellsworth consortium - Siegert, Martin; Behar, A.; Bentley, Michael; Blake, David; Bowden, Stephen; Christoffersen, Poul; Cockell, Charles; Corr, Hugh; Cullen, David C.; Edwards, Howell; Ellery, A.; Ellis-Evans, Cynan; et al. (Reviews in Environmental Science and Bio/Technology, 2007)
Antarctic subglacial lakes have, over the past few years, been hypothesised to house unique forms of life and hold detailed sedimentary records of past climate change. Testing this hypothesis requires in situ examinations. The direct measurement of subglacial lakes has been considered ever since the largest and best-known lake, named Lake Vostok, was identified as having a deep water-column. The Subglacial Antarctic Lake Environments (SALE) programme, set up by the Scientific Committee on Antarctic Research (SCAR) to oversee subglacial lakes research, state that prior exploration of smaller lakes would be a "prudent way forward". Over 145 subglacial lakes are known to exist in Antarctica, but one lake in West Antarctica, officially named Ellsworth Subglacial Lake (referred to hereafter as Lake Ellsworth), stands out as a candidate for early exploration. A consortium of over 20 scientists from seven countries and 14 institutions has been assembled to plan the exploration of Lake Ellsworth. An eight-year programme is envisaged: 3 years for a geophysical survey, 2 years for equipment development and testing, 1 year for field planning and operation, and 2 years for sample analysis and data interpretation. The science experiment is simple in concept but complex in execution. Lake Ellsworth will be accessed using hot water drilling. Once lake access is achieved, a probe will be lowered down the borehole and into the lake. The probe will contain a series of instruments to measure biological, chemical and physical characteristics of the lake water and sediments, and will utilise a tether to the ice surface through which power, communication and data will be transmitted. The probe will pass through the water column to the lake floor. The probe will then be pulled up and out of the lake, measuring its environment continually as this is done. Once at the ice surface, any water samples collected will be taken from the probe for laboratory analysis (to take place over subsequent years). The duration of the science mission, ...